73Ge, 119Sn and 207Pb: general cooperative effects of single atom ligands on the NMR signals observed in tetrahedral [MXnY4−n] (M = Ge, Sn, Pb; 1 ≤ n ≤ 4; X, Y = Cl, Br, I) coordination compounds of heavier XIV group elements. Issue 9 (9th February 2017) - Benedetti, M.; De Castro, F.; Fanizzi, F. P.
Abstract : An inverse linear relationship between 73 Ge, 119 Sn and 207 Pb NMR chemical shifts and the sum of ionic radii of coordinated halides has been found in [MX n Y m ] (M = Ge, Sn, Pb; n + m = 4; X, Y = Cl, Br, I) compounds. Abstract : An inverse linear relationship between 73 Ge, 119 Sn and 207 Pb NMR chemical shifts and the overall sum of ionic radii of coordinated halido ligands has been discovered in tetrahedral [MX n Y4− n ] (M = Ge, Sn, Pb; 1 ≤ n ≤ 4; X, Y = Cl, Br, I) coordination compounds. This finding is consistent with a previously reported correlation found in octahedral, pentacoordinate and square planar platinum complexes. The effect of the coordinated halido ligands acting on the metal as shielding conducting rings is therefore confirmed also by 73 Ge, 119 Sn and 207 Pb NMR spectroscopy.